In silico structural characterisation of Plasmodium falciparum dihydro-6-hydroxymethylpterin pyrophosphokinase dihydropteroate synthase (PPPK-DHPS) - Joubert, Fourie (University of Pretoria, 2013)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2005.